2001
DOI: 10.1074/jbc.m100355200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Substrate Specificity-conferring Amino Acid Residues of 4-Coumarate:Coenzyme A Ligase Allows the Rational Design of Mutant Enzymes with New Catalytic Properties

Abstract: 4-Coumarate:coenzyme A ligases (4CLs) generally use, in addition to coumarate, caffeate and ferulate as their main substrates. However, the recently cloned Arabidopsis thaliana isoform At4CL2 is exceptional because it has no appreciable activity with ferulate. On the basis of information obtained from the crystal structure of the phenylalanine-activating domain of gramicidin S-synthetase, 10 amino acid residues were identified that may form the substrate binding pocket of 4CL. Among these amino acids, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 24 publications
0
74
0
Order By: Relevance
“…Pv4CL had conserved motif (long bar-AMP binding domain, SSGTTGLPKGV; short bar-GEICIRG). 24,25) In addition, the phylogenetic tree showed that the Pv4CL sequence was homologous to other C4H sequences (Supplemental information Fig. S3).…”
Section: Fig 3 Multiple Alignments Of the Amino Acid Sequence Of Pvmentioning
confidence: 99%
“…Pv4CL had conserved motif (long bar-AMP binding domain, SSGTTGLPKGV; short bar-GEICIRG). 24,25) In addition, the phylogenetic tree showed that the Pv4CL sequence was homologous to other C4H sequences (Supplemental information Fig. S3).…”
Section: Fig 3 Multiple Alignments Of the Amino Acid Sequence Of Pvmentioning
confidence: 99%
“…1, all except sinapate are efficiently activated by numerous 4CLs from various sources, whereas sinapate has so far been converted with appreciable efficiency, apart from crude or partially purified protein extracts (2,5,(8)(9)(10), by just one pure heterologously expressed isoenzyme, Gm4CL1 from soybean (Glycine max L.) (11). A recent combination of structural, biochemical, and mutational analyses using At4CL2 from Arabidopsis thaliana as a test case revealed that the substrate-binding pocket of this and all other 4CLs with the same specificity-determining amino acid code is too small to accommodate sinapate (12,13). Directed mutations enlarging this pocket to a size similar to that realized in Gm4CL1 indeed led to the expected broadening of the substrate specificity, including the conversion of sinapate (13).…”
mentioning
confidence: 99%
“…The 4CL family in Arabidopsis has four members that are distantly related to 4CL-like proteins. However, both classes have two conserved box I and box II motifs, the amino acid residues in-between determining the substrate specificity of the enzyme (Stuible and Kombrink 2001;Schneider et al 2003). Both motifs can be identified in the O7 protein, with the 12-bp deletion of the o7-ref allele mapping between the two ( Figure 2B).…”
Section: Discussionmentioning
confidence: 97%
“…The o7-6 allele, on the other hand, abolished a lysine residue in the C-terminal domain as a consequence of the Ds insertion at amino acid 496. This lysine residue is important in adenylate formation (Stachelhaus et al 1999;Stuible and Kombrink 2001;Schneider et al 2003), thus probably causing an altered functionality of the O7-6 protein. At3g48990, which is the o7 homolog in Arabidopsis (Figure 5), grouped with yeast fatty acid CoA ligase and has been proposed to have the same function (Cukovic et al 2001).…”
Section: Discussionmentioning
confidence: 99%